2023
DOI: 10.1080/07853890.2023.2192519
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different inhalation therapies on less symptomatic chronic obstructive pulmonary disease patients in a Chinese population: a real-world study

Abstract: Background The Global Initiative for Chronic Obstructive Lung Disease (GOLD) document suggests that patients with chronic obstructive pulmonary disease (COPD) should be divided into a less symptomatic group. Moreover, single-inhaled drugs are recommended as initial inhalation therapy for them. However, many less symptomatic patients are provided double or triple-inhaled drugs as initial therapy in the real world. This study aimed to describe the inhalation prescriptions and compare the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“… 18 19 However, our previous study found that there were no significant differences in exacerbation, hospitalization, and mortality during the follow-up among different inhalation therapies on less symptomatic COPD patients. 20 This study also confirmed that the patients in Groups A and C treated with LABA + LAMA or LABA + LAMA + ICS did not achieve better outcomes than patients treated with LAMA or LABA + ICS. Therefore, merging Groups C and D into Group E and recommending LABA + LAMA or LABA + LAMA + ICS as the initial inhalation therapy must be considered.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“… 18 19 However, our previous study found that there were no significant differences in exacerbation, hospitalization, and mortality during the follow-up among different inhalation therapies on less symptomatic COPD patients. 20 This study also confirmed that the patients in Groups A and C treated with LABA + LAMA or LABA + LAMA + ICS did not achieve better outcomes than patients treated with LAMA or LABA + ICS. Therefore, merging Groups C and D into Group E and recommending LABA + LAMA or LABA + LAMA + ICS as the initial inhalation therapy must be considered.…”
Section: Discussionsupporting
confidence: 75%
“…Finally, some studies have shown that the real-world 10 journals.sagepub.com/home/tar TherapeuTic advances in respiratory disease prescriptions of initial inhalation therapy for COPD patients were not consistent with GOLD reports and the causes including pulmonary function, poor familiarity with recommendations, low self-efficacy, and time constraints might have an influence on the future exacerbation and mortality. [20][21]…”
Section: Discussionmentioning
confidence: 99%
“…Notably, 80% of the original studies required subjects to have a smoking history of no less than 10 pack-years, which may lead to bias in the evidence for younger patients, mild status (GOLD 1) (relevant trial is already underway 53 ), or never smokers. Despite some studies suggesting the benefit of triple therapy may not be related to age or lung function, 54 , 55 the evidence appears to be insufficient. Furthermore, a SR confirmed the absolute benefit appeared to be greater for ex-smokers; 56 however, we have not yet found whether there is a difference in benefit for never-smoking patients.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study confirmed that the future exacerbation and mortality showed no significant differences among different inhalation therapies in patients with less symptomatic COPD. 26 It implied that mono-LAMA should be recommended to the non-frequent exacerbation patients with less symptomatic COPD as the initial inhalation therapy.…”
Section: Discussionmentioning
confidence: 99%